2003
DOI: 10.1590/s0074-02762003000300025
|View full text |Cite
|
Sign up to set email alerts
|

Apparent competition through facilitation between Melanoides tuberculata and Biomphalaria glabrata and the control of schistosomiasis

Abstract: Interactions between two species that result in reduced growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…However, species of the family Thiaridae has caused significant effects on native mollusks (Pointier & Augustin, 1999;Guimarães et al, 2001;Giovanelli et al, 2003Giovanelli et al, , 2005. The small number of individuals of Pomacea lineata and Biomphalaria straminea, which presented densities below 100 ind.m -2 , intensifies the effect of the exotic species M. tuberculata, reducing the native populations in the reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…However, species of the family Thiaridae has caused significant effects on native mollusks (Pointier & Augustin, 1999;Guimarães et al, 2001;Giovanelli et al, 2003Giovanelli et al, , 2005. The small number of individuals of Pomacea lineata and Biomphalaria straminea, which presented densities below 100 ind.m -2 , intensifies the effect of the exotic species M. tuberculata, reducing the native populations in the reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…associations with pulmonate snails and parasitism by trematodes can lead to the death of native birds and mammals that live and feed on the lake. an example of an associated trematode, Centrocestus formosanus -that completes part of its lifecycle within the digestive gland of M. tuberculatusspreads heavy infections to fish and ducks in the Usa (brandt, 2000 (Guimarães et al, 2001;Giovanelli et al, 2003). pointier (1993) and pointier et al (1989,1991,1993) showed the ability of this species to control and even exclude Biomphalaria in some islands of the French West indies.…”
Section: Discussionmentioning
confidence: 99%
“…regions that it has invaded include north america (Murray, 1964), south america (pointier et al, 1994;de Marco, 1999) and French polynesia (pointier & Marquet, 1990). in brazil, the first record of M. tuberculatus was in santos, são paulo state (vaz et al, 1986) and nowadays these invasive aquatic snails have been reported in the states of Minas Gerais (carvalho, 1986;silva et al, 1994;de Marco, 1999de Marco, ), paraíba (paz et al, 1995, rio de Janeiro (thiengo et al, 1998, 2002a, 2002bGiovanelli et al, 2003), ceará (Mello & cordeiro, 1999(Mello & cordeiro, ), paraná (pereira, 2000 and Federal district (Monteiro & dias, 1980;vieira, 1990;Garcez & Martins-silva, 1997;Medeiros, 1997). Fernandez et al (2003) still report M. tuberculatus in the states of pará, tocantins, piauí, paraíba, pernambuco, rio Grande do norte, bahia, Goiás, Mato Grosso, Mato Grosso do sul, paraná and santa catarina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…are frequent, since the former is a biological control agent for schistosomiasis and can reduce the population of gastropods of the genus Biomphalaria, the intermediate hosts of Schistosoma mansoni (Giovanelli et al, 2003;Guimarães et al, 2001;Pointier, 2001). However, studies indicate that M. tuberculatus also acts as a primary intermediate host of parasitic trematodes of respiratory and hepatic systems in humans (Paragonimus westermani and Clonorchis sinensis) (Souza and Lima, 1990;Vaz et al, 1986;Boaventura et al, 2002).…”
Section: Ecologymentioning
confidence: 99%